Mortality and cardiorenal outcomes among heart failure patients with zinc deficiency: a multicenter retrospective cohort study of 8,290 patients - Lin, Yu-Min; Tu, Wan-Ling; Hung, Kuo-Chuan; Yu, Tsung; Wu, Jheng-Yan; Lai, Chih-Cheng (Frontiers in Nutrition, 2025)
ObjectiveThis study aimed to examine the association between zinc deficiency (ZD) and the clinical outcomes in patients with heart failure (HF).MethodsThis multicenter retrospective cohort study used the TriNetX network to identify adult patients with HF between January 1, 2010, and January 31, 2025. Patients with serum zinc levels below 70 μg/dL (ZD group) were propensity score-matched to those with levels between 70 and 120 μg/dL (control group) to minimize confounding. Primary outcomes included all-cause mortality, major adverse cardiovascular events (MACEs), and major adverse kidney events (MAKEs). Secondary outcome was all-cause hospitalization.ResultsAfter matching, each group comprised 4,145 patients with well-balanced baseline characteristics. During the 1-year follow-up, the ZD group was associated with higher risks of all-cause mortality (hazard ratio [HR]: 1.46, 95% confidence interval [CI]: 1.29–1.66), MACEs (HR: 1.46, 95% CI: 1.30–1.64), and MAKEs (HR: 1.51, 95% CI: 1.34–1.70), as well as an higher risk of all-cause hospitalization (HR: 1.24, 95% CI: 1.16–1.32).ConclusionZinc deficiency in patients with HF is associated with increased risks of mortality, cardiovascular and kidney-related adverse events, and hospitalization. These findings highlight the potential clinical importance of zinc assessment and management in HF care.